Implementation of Digital Literacy in Indonesia Early Childhood Education - Sri Tatminingsih (International Journal of Emerging Issues in Early Childhood Education, 2022)
Digital literacy is a person's interests, attitudes, abilities, and skills in using digital technology-based devices. These skills are used to access, manage, integrate, analyze and evaluate the information needed and obtained, build new knowledge and create relationships or communication with others to participate effectively in society. This study aims to explore and explain the application of digital literacy in Early Childhood Education (ECE) institutions. The research method is descriptive quantitative with a survey technique. The instrument used is a questionnaire in the form of a Google-Form (G-Form) which is distributed online via Instagram, WhatsApp, and email. The population is ECE teachers, and a sample of 318 ECE teachers from various provinces was collected randomly. The data collected were analyzed descriptively with simple quantification. The results of the study indicate that the application of digital literacy in ECE can be implemented in a limited way and the implementation process must involve teachers and parents/guardians. The recommendation conveyed was the need for strict supervision for the implementation of digital literacy in early childhood.